Republic of Tajikistan : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2007)
This report on the Observance of Standards and Codes on Fiscal Transparency for the Republic of Tajikistan analyzes fiscal transparency practices against the requirements of the IMF Code of Good Practices on Fiscal Transparency. In the context of sectoral reforms, the authorities intend to promote fee-supported services of budget-financed institutions. In several areas, Tajikistan meets fiscal transparency requirements partially, but further reforms could bring it closer to meeting international best practices. Effective implementation of recently enacted laws will be crucial to achieving the level of transparency stipulated in legislation.